ANALISIS PENGARUH FAKTOR MOBILITAS TERHADAP KEJADIAN MALARIA IMPOR DI WILAYAH KERJA PUSKESMAS PANDEAN KABUPATEN TRENGGALEK - RULIK TRI ANGGRAINI, 101214153057 (2014)
The proportion of imported malaria cases in East Java had increased, from 48.04% in 2007 to 99.91% in 2013. Pandean was Health Center with the highest imported malaria case in Trenggalek, with spesific sufferers were workers in circular mobility. The study aimed to analyze the influence of mobility factors to imported malaria incidence in Pandean. This study was an analytic observational using case-control design. The ratio of cases and controls is 1:2. The number of cases was 45 people and the controls were 90 workers in circular mobility who has ever outside the Java in 2013. The data was analyzed using logistic regression. The dependent variable was the incidence of imported malaria, while the independent variable was mobility factors (destination area at risk, frequency and length of stay) and prevention behavior (not using repellant, not using insecticide nets, having activities outside at night, not wearing long clothes in the evening, not wearing long clothes at work and not taking chemoprophylaxis). The results of this study were 1). Destination area at risk, p=0,003; 2). Not using insecticide nets, p = 0.003; 3). Having activities outside at night, p = 0.016; 4). Not taking chemoprophylaxis (p = 0.004) influence on the imported malaria. Confounding variables were the type of jobs at risk, history of malaria, high frequency mobility, short length of stay, not using repellent, not wearing long clothes in the evening, not wearing long clothes at work. The conclusion of this study showed that destination area at risk, having activities outside at night, not using insecticide nets, not taking chemoprophylaxis influence on the incidence of imported malaria.